Benefits Of Job Rotation: Systematic Literature Review (SLR) - Isymayati Ash Shiddiqy; Sopiah Sopiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this study is to analyze the benefits of having a rotational system of work in a company. The method used in this research is PRISMA. (Preferred Reporting Items for Systematic Review and Meta-Analyses). The data sources used were obtained through the Publish or Perish software that covers Google scholar and ScienceDirect with the search year range 2018-2023, then the results of 347 journals. Using the inclusion and exclusion criteria, then the 10 journal to be analyzed. The results of this literature review study show that with the rotation of work applied to the organization or company, many positive aspects are obtained such as increased employee motivation, reduced boredom, and improved employee performance.